Modifikasi Kombinasi Elektrokoagulasi – Adsorpsi untuk Menyisihkan Fosfat dan TSS pada Limbah Laundry - Cello Raka Pramastya (Fakultas Teknik, 2023)
The home industry laundry has grown rapidly. However, the growth of this industry has also led to an increase in the volume of laundry wastewater that is discharged into water bodies. This can affect the condition of water bodies, especially since the waste contains phosphates as detergent builders. Therefore, an effective wastewater treatment technology is needed. This research aims to analyze the efficiency of the modified electrocoagulation-adsorption reactor in reducing the concentration of phosphate and TSS in laundry wastewater. Laundry wastewater was flowed at a rate of 0.2 L/minute in the electrocoagulation process with a current strength of 5 A for 60 minutes, followed by column adsorption for 90 minutes conducted in one experimental reactor. Aluminum electrodes and zeolite adsorbent media were used in this experiment. The variables measured were the sampling time intervals between 150-300 minutes with a 30-minute interval. The research results show that the modification of the electrocoagulation-adsorption reactor is capable of reducing the concentration of phosphate and TSS in laundry wastewater. The best efficiency for phosphate reduction occurred at 210 minutes with an efficiency of 97.67%. Meanwhile, the optimal TSS reduction occurred at 300 minutes with an efficiency of 84.26%.